Small decreases in biventricular pacing percentages are associated with multiple metrics of worsening heart failure as measured from a cardiac resynchronization therapy defibrillator. (15th July 2021) - Cao, Michael; Stolen, Craig M.; Ahmed, Rezwan; Schloss, Edward J.; Lobban, John H.; Kwan, Brian; Varma, Niraj; Boehmer, John P.
Abstract: Background: Lower BiVentricular (BiV) pacing percentages have been associated with significantly worse survival in patients with chronic heart failure (HF). However, the pathophysiology behind this observation has not been further delineated. This analysis evaluated whether small incremental decreases in BiV pacing percentages were associated with worse measures, related to HF physiology using individual sensor trends and the HeartLogic composite index. Methods: Sensor data was obtained from 900 ambulatory HF patients with implanted CRT devices. The percent of cardiac cycles with BiV pacing was assessed for periods (median = 7.3 days) between data downloads (median = 55 periods/patient). Results: The third heart sound (S3), respiration rate, RSBI, and night-time heart rate were significantly elevated with sub-optimal pacing (<98%), while the first heart sound (S1), thoracic impedance, and activity were significantly lower. All sensor changes were in the direction associated with worsening HF. While IN the HeartLogic alert state (threshold above an Index of 16) the odds of optimal BiV pacing (≥98%) were less than when OUT of the HeartLogic alert state for a given subject (OR: 0.655; 95% CI: 0.626–0.686; p < 0.0001). The percent BiV pacing was reduced and the HeartLogic Index was increased in the periods surrounding HFhospitalizations. Conclusion: Lower BiV pacing percent is associated with multiple sensor changes indicative of worsening HF, and patients in HeartLogic alert are more likely to have suboptimal BiV pacing. Collectively, these data provide strong evidence that even small decreases in BiV percent pacing can lead to worsening HF. Highlights: Deteriorating sensor trends, associated heart failure worsening, were found with small decrements in BiV percent pacing. Patients in HeartLogic alert are more likely to have suboptimal BiV pacing. The percent BiV pacing was reduced, and the HeartLogic index was increased, preceding heart failure hospitalizations. These observations support the recommendation to maximize BiV percent pacing, to improve the heart failure condition.